2018
DOI: 10.1371/journal.pone.0198768
|View full text |Cite
|
Sign up to set email alerts
|

Raltegravir plus abacavir/lamivudine in virologically suppressed HIV-1-infected patients: 48-week results of the KIRAL study

Abstract: BackgroundLong-term combination antiretroviral therapy often results in toxicity/tolerability problems, which are one of the main reasons for switching treatment. Despite the favorable profile of raltegravir (RAL), data on its combination with abacavir/lamivudine (ABC/3TC) are scarce. Based on clinical data, we evaluated this regimen as a switching strategy.DesignMulticenter, non-controlled, retrospective study including all virologically suppressed HIV-1-infected patients who had switched to RAL+ABC/3TC.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 28 publications
1
4
0
1
Order By: Relevance
“…9 The KIRAL study, a recent multicentre, non-controlled, retrospective study, assessed the efficacy of ABC/3TC plus RAL in 380 virologically-suppressed patients, showing a high virological suppression rate at 48 weeks (97.6% of subjects with HIV-RNA <50 copies/mL). 10 With regard to the metabolic profile, as already mentioned, we observed a significant difference in triglycerides between mean values before the switch to ABC/3TC plus RAL and mean values at the latest measurement. We have therefore differentiated subjects according to the previous regimen: in the patients who switched from PI-based regimens, we observed a significant improvement of the lipid profile, particularly a decrease of total cholesterol and triglycerides.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…9 The KIRAL study, a recent multicentre, non-controlled, retrospective study, assessed the efficacy of ABC/3TC plus RAL in 380 virologically-suppressed patients, showing a high virological suppression rate at 48 weeks (97.6% of subjects with HIV-RNA <50 copies/mL). 10 With regard to the metabolic profile, as already mentioned, we observed a significant difference in triglycerides between mean values before the switch to ABC/3TC plus RAL and mean values at the latest measurement. We have therefore differentiated subjects according to the previous regimen: in the patients who switched from PI-based regimens, we observed a significant improvement of the lipid profile, particularly a decrease of total cholesterol and triglycerides.…”
Section: Discussionsupporting
confidence: 66%
“…Similarly to our study, in other studies the switch to ABC/3TC plus RAL led to an improvement in lipid levels and liver function, particularly if the previous regimen contained a PI. 6,7,10,11 In the treatment-naı¨ve group, all five patients achieved viral suppression at the latest measurement, suggesting the efficacy of ABC/3TC plus RAL among treatment-naı¨ve patients. Three patients had pretreatment viral loads > 100,000 copies/mL, and all of them achieved viral suppression.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Clinical trials have demonstrated that patients with suppressed viral loads maintain high rates of virologic suppression after switching to INSTI-containing regimens. 5,14,15 Some observational studies have also shown good virologic outcomes in suppressed patients switching to RAL, [16][17][18] one study in patients switching to EVG, 9 and one in patients switching to DTG. 19 One cohort study reported low failure rates over two years after switching while suppressed to an INSTI-based regimen, including RAL, DTG, and EVG, though it did not compare INSTI agents.…”
Section: Discussionmentioning
confidence: 99%
“…Llama la atención que, pese a la mejoría significativa del perfil lipídico, sólo una proporción menor de los pacientes logró normalizarlo. El efecto de la modificación de la TAR a RAL sobre el perfil lipídico de los pacientes con supresión virológica ha sido menos consistente en los estudios de cohorte "de la vida real" (ECVR) que han sido publicados [14][15][16][17] . Los cambios reportados en los TG van desde descensos no significativos (estudios ORASWIRAL 15 y KIRAL 16 ) hasta caídas de 26,1% del valor basal 17 .…”
Section: Discussionunclassified